Enhanced Osteogenic and Vasculogenic Differentiation Potential of Human Adipose Stem Cells on Biphasic Calcium Phosphate Scaffolds in Fibrin Gels - Fransisca A. S. van Esterik; Behrouz Zandieh-Doulabi; Cornelis J. Kleverlaan; Jenneke Klein-Nulend (Hindawi Limited, 2016)
For bone tissue engineering synthetic biphasic calcium phosphate (BCP) with a hydroxyapatite/β-tricalcium phosphate (HA/β-TCP) ratio of 60/40 (BCP60/40) is successfully clinically applied, but the high percentage of HA may hamper efficient scaffold remodelling. Whether BCP with a lower HA/β-TCP ratio (BCP20/80) is more desirable is still unclear. Vascular development is needed before osteogenesis can occur. We aimed to test the osteogenic and/or vasculogenic differentiation potential as well as degradation of composites consisting of human adipose stem cells (ASCs) seeded on BCP60/40 or BCP20/80 incorporated in fibrin gels that trigger neovascularization for bone regeneration. ASC attachment to BCP60/40 and BCP20/80 within 30 min was similar (>93%). After 11 days of culture BCP20/80-based composites showed increased alkaline phosphatase activity and DMP1 gene expression, but not RUNX2 and osteonectin expression, compared to BCP60/40-based composites. BCP20/80-based composites also showed enhanced expression of the vasculogenic markers CD31 and VEGF189, but not VEGF165 and endothelin-1. Collagen-1 and collagen-3 expression was similar in both composites. Fibrin degradation was increased in BCP20/80-based composites at day 7. In conclusion, BCP20/80-based composites showed enhanced osteogenic and vasculogenic differentiation potential compared to BCP60/40-based composites in vitro, suggesting that BCP20/80-based composites might be more promising for in vivo bone augmentation than BCP60/40-based composites.